Establishment of Regional Regulations For Coastal Area Rehabilitation As An Environmental Restoration Effort In Buru District - Tuhulele, Popy; Anwar, Arman; Waas, Armelia Febriyanti (Batulis Civil Law Review, 2024)
Introduction: Research entitled "Establishment of Regional Regulations for Coastal Area Rehabilitation as an Environmental Recovery Effort in Buru Regency". Purposes of the Research: The specific aim of this research is to find out and analyze the impact of traditional mining activities on environmental damage in coastal areas, especially in Kayeli Bay, Buru Regency as the estuary of rivers affected by mining activities and to find and analyze the importance of establishing Regional Rehabilitation Regulations as an effort to restore the marine and coastal environment. in Buru Regency.Methods of the Research: This research uses an exploratory type of empirical normative research. This research approach is a statutory approach, a concept approach and a case approach. The data collection techniques used in this research were interviews and literature study.Results of the Research: Mining activities using dangerous chemicals carried out over a period of 23 years have had a major impact on the environmental conditions of Buru Regency. Environmental pollution and destruction not only occurs in mining areas but also land, river flows, bays, coasts and seas which are the final estuaries of mining remains. Kayeli Bay is an important area for fishing, to support the daily lives of around 50,000 village communities. coast. Kaiely Bay is located between 3º 15' 55” - 3º 22' 50” S and 127º 01'35”-127º 01'35” E and is an estuary in nature because it is influenced by the surrounding land, through runoff that enters through rivers that empties into the bay. Continuous abundance of nutrients causes an increase in water fertility. On the other hand, Kaiely Bay is also able to supply and fertilize the surrounding waters with nutrients and a high concentration of chlorophyll-a, namely > 6 mg/L.